2014
DOI: 10.1148/radiol.14131104
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Contrast Material–induced Nephropathy after Neuroendovascular Procedures

Abstract: Risk of developing CIN CM-induced nephropathy is relatively low in patients who undergo neuroendovascular procedures with CM contrast material doses of 250 mL or greater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
0
12
1
1
Order By: Relevance
“…Recent studies evaluating the propensity of contrast exposure to induce AKI in noncardiovascular settings demonstrated that intravenous contrast is not an independent risk factor for AKI, dialysis, or mortality. [6][7][8] Importantly, because studies linking CM use to AKI in the setting of pPCI lack a control group in which CM was not administered, it is impossible to distinguish CM-dependent AKI from multiple additional risk factors other than exposure to contrast media. 9 Consequently, studies that include ST-segmentelevation myocardial infarction (STEMI) patients who were not exposed to CM are desirable.…”
mentioning
confidence: 99%
“…Recent studies evaluating the propensity of contrast exposure to induce AKI in noncardiovascular settings demonstrated that intravenous contrast is not an independent risk factor for AKI, dialysis, or mortality. [6][7][8] Importantly, because studies linking CM use to AKI in the setting of pPCI lack a control group in which CM was not administered, it is impossible to distinguish CM-dependent AKI from multiple additional risk factors other than exposure to contrast media. 9 Consequently, studies that include ST-segmentelevation myocardial infarction (STEMI) patients who were not exposed to CM are desirable.…”
mentioning
confidence: 99%
“…They found that only age >75 years was associated with the development of CI-AKI 22. Prasad et al 23 found that the proportion of patients with diabetes was higher among those who developed CI-AKI in patients undergoing a neuroendovascular procedure. Another study showed that among patients with acute ischemic stroke, patients with CI-AKI had a higher baseline serum creatinine level 21.…”
Section: Discussionmentioning
confidence: 99%
“…Altmann et al recommended using the ratio of contrast media volume to creatinine clearance as a predictor for CIN (18). Subsequently, Laskey et al and Prasad et al reported contrast media to creatinine clearance ratios greater than 3.7 and 2.6, respectively, as significant and independent predictors of CIN after percutaneous coronary intervention and neurovascular procedures (19,20). Placed in perspective versus IV contrast media dosing, for a patient with renal insufficiency and a creatinine clearance of 60 mL/min, these thresholds are 222 and 156 mL, respectively.…”
Section: Discussionmentioning
confidence: 99%